2011
DOI: 10.1158/1535-7163.mct-11-0218
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB Is Required for Smac Mimetic-Mediated Sensitization of Glioblastoma Cells for γ-Irradiation–Induced Apoptosis

Abstract: Evasion of apoptosis contributes to radioresistance of glioblastoma, calling for novel strategies to overcome apoptosis resistance. In this study, we investigated the potential of the small molecule Smac mimetic BV6 to modulate radiosensitivity of glioblastoma cells. Here, we identify a novel proapoptotic function of NF-kB in g-irradiation-induced apoptosis of glioblastoma cells by showing, for the first time, that NF-kB is critically required for Smac mimetic-mediated radiosensitization. BV6 significantly inc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 34 publications
4
64
0
Order By: Relevance
“…First, we confirmed the increased activity of NF-κB in RPMI 8226 cells under SD ( Figure 7C and 7D), which was consistent with a report that cell stress stimulates NF-kB activation and decreases pro-death signal-induced apoptosis [24] . Thus, excreting ZNF224 by shedding MVs did not decrease the activity of the NF-κB signaling pathway in the parent RPMI 8226 cells.…”
Section: Validation Of Enriched Znf224 Protein In Sd Mvssupporting
confidence: 91%
“…First, we confirmed the increased activity of NF-κB in RPMI 8226 cells under SD ( Figure 7C and 7D), which was consistent with a report that cell stress stimulates NF-kB activation and decreases pro-death signal-induced apoptosis [24] . Thus, excreting ZNF224 by shedding MVs did not decrease the activity of the NF-κB signaling pathway in the parent RPMI 8226 cells.…”
Section: Validation Of Enriched Znf224 Protein In Sd Mvssupporting
confidence: 91%
“…7 Furthermore, we previously reported that inhibition of IAP proteins by Smac mimetic can prime GBM cells for TRAIL-, chemotherapy-or irradiation-induced apoptosis. 21,22,43,44 The notion that Smac mimetic can exert non-apoptotic functions under certain conditions is supported by our recent findings showing that Smac mimetics can promote migration and invasion of GBM cells at a non-lethal concentration. 45 As tumor heterogeneity comprising CSLCs as well as more mature GBM cells is a characteristic feature of GBM, Smac mimetics may support migration/invasion or differentiation within the same tumor, depending, for example, on the cell type.…”
Section: Resultsmentioning
confidence: 66%
“…15 Previously, we reported that IAP inhibitors increase the radiosensitivity of GBM cells including GBM CSLCs by lowering the threshold for apoptosis induction. 21,22 However, the question whether or not IAP inhibitors also regulate additional cellular functions beyond apoptosis in GBM CSLCs has not yet been addressed. Therefore, in this study we investigated the role of the Smac mimetic BV6 23 in the regulation of differentiation of GBM CSLCs.…”
mentioning
confidence: 99%
“…31,48,49 Our findings showing that BV6 cooperates together with Obatoclax to induce cell death in CLL cells, but not together with ABT-263 may be related to the differential activity profiles of these BH3 mimetics, as Obatoclax antagonizes BCL-2, BCL-xL, BCL-W and MCL-1, whereas ABT-263 targets BCL-2, BCL-xL and BCL-W, but not MCL-1. 50 Single-agent cytotoxicity of Smac mimetic compounds has been reported for CLL, 40 multiple myeloma or 2, 12, 17, 39) were treated for indicated times with 10 mM BV6, 1 mM Staurosporine and 20 mM zVAD.fmk alone or in combination.…”
Section: Discussionmentioning
confidence: 80%
“…BV6 modulates genes related to programmed cell death, NF-jB and redox signaling across tumor entities Based on our previous data showing that BV6-stimulated activation of transcription factors such as NF-jB and IRF1 is critically required for BV6-induced apoptosis, [30][31][32][33][34] we performed gene expression profiling to identify genes that are specifically regulated in BV6-responsive CLL samples. A total of 1,068 genes were found to be significantly differentially expressed between the BV6-treated and DMSO control group (p < 0.05).…”
Section: Bv6 Induces Cell Death In Primary Cll Cells Irrespective Of mentioning
confidence: 99%